Azure data engineering cookbook : get well versed with different data engineering techniques with Azure data services usinf this recipe-based guide /: get well versed with different data engineering techniques with Azure data services usinf this recipe-based guide. (2022) - Venkatesan, Nagaraj; Osama, Ahmad
No abstract available